Neighborhood context and the pretrial process: do defendants face adverse outcomes due to their home address? - St. Louis, Stacie (Criminal justice policy review, 2020)
When extralegal factors correlate with differences in bond amount and pretrial detention, justice may be compromised. Prior research has identified disparity related to defendant characteristics, such as income and race. This article offers insight into a less explored source of disparity, neighborhood context, and a particularly disadvantaged population, defendants, or pretrial detainees, unable to afford their bail in court and booked into a county jail. Considering the desire for community safety, the difficulty of predicting dangerousness and court attendance, and the impact of ecological factors on other court outcomes, it is hypothesized that neighborhood context heightens disparity in the pretrial process. Findings support this argument. Offense elements best predict bond amount; however, there exists disparity based on neighborhood characteristics. When assessing the same factors in relation to detention length, bond amount is not significant, but rather individual- and neighborhood-level characteristics. Implications are discussed in light of current bail reform efforts.